Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1.\left(x+4\right)^2-\left(x-1\right)\left(x+1\right)=16\Leftrightarrow x^2+8x+16-x^2+1=16\)
\(\Leftrightarrow8x=-1\Leftrightarrow x=-\frac{1}{8}\)
\(2.\left(x-1\right)^2+\left(x+3\right)^2+2\left(x-1\right)\left(x+3\right)=4\Leftrightarrow\left(x-1+x+3\right)^2=4\)
\(\Leftrightarrow\left(2x+2\right)^2=4\Leftrightarrow\orbr{\begin{cases}2x+2=2\\2x+2=-2\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=-2\end{cases}}\)
3.\(\left(x-1\right)^2-x\left(x-1\right)=0\Leftrightarrow\left(x-1\right)\left[\left(x-1\right)-x\right]=0\Leftrightarrow x-1=0\Leftrightarrow x=1\)
\(4.\left(3x-1\right)^2+\left(5x-2\right)^2-2\left(3x-1\right)\left(5x-2\right)=9\Leftrightarrow\left(3x-1-5x+2\right)^2=9\)
\(\Leftrightarrow\left(2x-1\right)^2=9\Leftrightarrow\orbr{\begin{cases}2x-1=3\\2x-1=-3\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
5.\(\left(x-1\right)\left(x^2+x+1\right)-x\left(x-2\right)\left(x+2\right)=5\Leftrightarrow x^3-1-\left(x^3-4x\right)=5\)
\(\Leftrightarrow4x=6\Leftrightarrow x=\frac{3}{2}\)
6.\(\left(x-1\right)^3-\left(x+3\right)\left(x^2-3x+9\right)+\left(x-2\right)\left(x+2\right)=2\)
\(\Leftrightarrow x^3-3x^2+3x-1-\left(x^3+27\right)+x^2-4=2\)
\(\Leftrightarrow-2x^2+3x-34=0\text{ vô nghiệm}\)
Bài 9.
d) \(a^2+b^2+c^2=ab+bc+ca\)
\(\Leftrightarrow2a^2+2b^2+2c^2-2ab-2bc-2ca=0\)
\(\Leftrightarrow a^2-2ab+b^2+b^2-2bc+c^2+c^2-2ca+a^2=0\)
\(\Leftrightarrow\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2=0\)
\(\Leftrightarrow\hept{\begin{cases}a-b=0\\b-c=0\\c-a=0\end{cases}}\Leftrightarrow a=b=c\).
Bài 10.
\(x^2+y^2-2x+4y+5=0\)
\(\Leftrightarrow x^2-2x+1+y^2+4y+4=0\)
\(\Leftrightarrow\left(x-1\right)^2+\left(y+2\right)^2=0\)
\(\Leftrightarrow\hept{\begin{cases}x-1=0\\y+2=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=1\\y=-2\end{cases}}\).
\(a,\left|x+3,4\right|+\left|x+2,4\right|+\left|x+7,2\right|=4x\)
\(\left|x+3,4\right|\ge0;\left|x+2,4\right|\ge0;\left|x+7,2\right|\ge0\)
\(< =>\left|x+3,4\right|+\left|x+2,4\right|+\left|x+7,2\right|>0\)
\(< =>4x>0\)
\(x>0\)
\(\hept{\begin{cases}\left|x+3,4\right|=x+3,4\\\left|x+2,4\right|=x+2,4\\\left|x+7,2\right|=x+7,2\end{cases}}\)
\(x+3,4+x+2,4+x+7,2=4x\)
\(x=13\left(TM\right)\)
\(b,3^{n+3}+3^{n+1}+2^{n+3}+2^{n+2}\)
\(3^n.27+3^n.3+2^n.8+2^n.4\)
\(3^n.30+2^n.12\)
\(\hept{\begin{cases}3^n.30⋮6\\2^n.12⋮6\end{cases}}\)
\(< =>3^n.30+2^n.12⋮6< =>VP⋮6\)
ta chuyển vế ,đc PT sau:
\(x^2+\left(m-7\right)x+\frac{12}{x}-m^2+3m=0\)
\(\Leftrightarrow x^2+mx-7x+\frac{12}{x}-m^2+3m=0\left(1\right)\)
thay x=3 vào PT (1) ta có:
\(\left(1\right)\Leftrightarrow9+3m-3.7+\frac{12}{3}-m^2+3m=0\)
\(\Leftrightarrow-m^2+6m-8=0\)
\\(\Leftrightarrow m^2-6m+8=0\)
\(\Leftrightarrow m^2-6m+9-1=0\)
\(\Leftrightarrow\left(m-3\right)^2-1=0\)
\(\Leftrightarrow\left(m-4\right).\left(m-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}m-4=0\\m-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}m=4\\m=2\end{cases}}}\)